2007
DOI: 10.2116/analsci.23.201
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Transfer between Two Near-Infrared Spectrometers Based on a Wavelet Packet Transform

Abstract: A standardization algorithm, called WPTS, which is based on a wavelet packet transform (WPT) and entropy criteria, is proposed to transfer spectra between two near-infrared spectrometers. First, the spectra of the standardization samples measured on both spectrometers are collected and the difference mean spectrum is calculated; then, a wavelet packet transform is performed and a best WPT-tree is generated, of which a node is selected to establish a transfer matrix. Once the transfer matrix has been built, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Since internal factors (e.g., detector performance, calibration quality, dispersion element and stability, stray light) are out of the instrument operator's control, all other possible external factors must be kept constant (Tan and Menglong, 2007;Feudale et al, 2002;Wüliams, 1987). On die basis of these criteria and on years of experience in spectroscopic measurements of soils, we established a strict protocol for spectroscopic soil measurements that works in both the field and the laboratory (hereafter termed TAU protocol).…”
Section: Protocol For Spectral Measurementsmentioning
confidence: 99%
“…Since internal factors (e.g., detector performance, calibration quality, dispersion element and stability, stray light) are out of the instrument operator's control, all other possible external factors must be kept constant (Tan and Menglong, 2007;Feudale et al, 2002;Wüliams, 1987). On die basis of these criteria and on years of experience in spectroscopic measurements of soils, we established a strict protocol for spectroscopic soil measurements that works in both the field and the laboratory (hereafter termed TAU protocol).…”
Section: Protocol For Spectral Measurementsmentioning
confidence: 99%
“…Many research groups (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) have studied the calibrations of NIR systems as problems of calibration transfer or standardization. For example, Wang et al (59) proposed direct standardization (DS) and piecewise direct standardization (PDS), and Shenk et al (60) developed an algorithm with wavelength index correction and spectral intensity correction, a patented method.…”
Section: Regarding the Calibration Transfer Methods Proposed Previouslymentioning
confidence: 99%
“…They found that normalized energy and entropy were suitable features for classification of ECG signals. Tan and Li (2007) proposed wavelet packet transform and entropy based criteria to transfer the spectral data between two spectrometers. Calibration transfer between two NIR spectrometers is a very challenging task due to the differences in instrumental responses and varying environmental conditions.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%